Mid-infrared to ultraviolet optical properties of InSb grown on GaAs by molecular beam epitaxy - D'Costa, Vijay Richard (2015)
Spectroscopic ellipsometry was used to investigate the optical properties of an InSb film grown on a GaAs (100) substrate, and to compare the optical properties of InSb film with those of bulk InSb. The film was grown by molecular beam epitaxy under conditions intended to form 90° misfit dislocations at the InSb-GaAs interface. The complex dielectric function obtained in a wide spectroscopic range from 0.06–4.6 eV shows the critical point transitions E 0, E 1, E 1 + Δ1, E′0 , and E 2. The amplitudes, energy transitions, broadenings, and phase angles have been determined using a derivative analysis. Comparing film and bulk critical point results reveal that the epitaxial film is nearly relaxed and has bulk-like optical characteristics.